Risks and Benefits of Dual Antiplatelet Therapy Beyond 12 Months After Coronary Stenting: A Prospective Randomized Cohort Study. Issue 22 (May 2016) - Dadjou, Yahya; Safavi, Salar; Kojuri, Javad
Abstract : Abstract: The optimal duration of dual antiplatelet therapy (DAT) after coronary stenting remains poorly define. The aim of this study was to evaluate the impact of longer than 24 months DAT in patients who received drug-eluting and bare-metal stents. A total of 1010 individuals who underwent elective, urgent or emergency coronary angioplasty with intended stent implantation at reference or specialized cardiac hospitals were randomized to receive long-term and short-term DAT to determine the benefits and adverse effects of long-term DAT. Total of 508 patients were randomized to long-term and 502 patients to <1 year DAT, and all of them were followed for more than 36 months for major adverse cardiac and cerebvascular events and bleeding major adverse cardiac and cerebvascular events (MACCE) Mean age of the 1010 patients (364 women and 646 men) was 60 years. Stent reocclusion occurred in 15 patients. Mean Syntax score was 23.00 ± 5.08 for whole samples, 25.00 ± 5.27 in 28 patients with MACCE and 23 ± 5.00 in 982 patients without MACCE ( P = 0.057). According to all specified bleeding definitions, clopidogrel therapy for >12 months was not associated with a greater risk of hemorrhage. A regimen of >12 months of clopidogrel therapy in patients who had received drug-eluting or bare-metal stents did not differ significantly from a regimen of <12 months on clopidogrel with regard to MACCE. Long-term DAT might not significantly affect the reduction in the risk of death from any cause, myocardial infarction, or stroke, and not associated with minor or major bleeding events.